THE INFLUENCE OF UNEMPLOYMENT AND ENTREPRENEURSHIP IN UPE STUDENTS - Noelia Closs Melgarejo, Daissy; Natalia Galeano Rejala, Lilian (Revista Gênero e Interdisciplinaridade, 2023)
At present one of the biggest difficulties that the country is going through corresponds to unemployment, mainly due to the lack of jobs in the professional field. This reality is not alien to people who are in the process of university education, who require a job to continue studying. In recent years, there has been a positive growth in entrepreneurship, which provides an opportunity to break into a changing market. The main objective of this research was to describe the relationship between unemployment and entrepreneurship in university students. The survey technique was applied through a questionnaire with closed questions to a population of 103 students of the Business Engineering career of the Universidad Privada del Este, Ciudad del Este Campus, corresponding to the period 2020. This research was developed under the paradigm of the approach quantitative and the level was descriptive. With the results of the data collection instrument, it was possible to understand that unemployment is one of the main factors that leads to starting your own business.